Immigration, fertility and human capital: A model of economic decline of the West - Leonid V. Azarnert (Bar-Ilan University, Department of Economics, 2010)
I show how the influences of unskilled immigration, differential fertility between immigrants and the local indigenous population, and incentives for investment in human capital combine to predict the decline of the West. In particular, indigenous low-skilled workers lose from unskilled immigration even if the indigenous lowskilled workers do not finance redistribution, do not compete with immigrants in the labor market, and do not compete with immigrants for publicly financed income transfers. For the economy at large, high-fertility unskilled immigrants and a lowfertility indigenous population result in economic decline through reduced human capital accumulation and reduced growth of per-capita output.
Keywords: D3; F22; J1; O4; 330; immigration; redistribution; ethnic diversity; fertility; human capital; economic growth; Einwanderung; Ungelernte Arbeitskräfte; Migranten; Fertilität; Bevölkerung; Bildungsinvestition; Einkommensumverteilung; Stagnation; Theorie; Westliche Staaten